OSS Reliability Measurement and Assessment - Yamada, Shigeru; Tamura, Yoshinobu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book analyses quantitative open source software (OSS) reliability assessment and its applications, focusing on three major topic areas: the Fundamentals of OSS Quality/Reliability Measurement and Assessment; the Practical Applications of OSS Reliability Modelling; and Recent Developments in OSS Reliability Modelling. Offering an ideal reference guide for graduate students and researchers in reliability for open source software (OSS) and modelling, the book introduces several methods of reliability assessment for OSS including component-oriented reliability analysis based on analytic hierarchy process (AHP), analytic network process (ANP), and non-homogeneous Poisson process (NHPP) models, the stochastic differential equation models and hazard rate models. These measurement and management technologies are essential to producing and maintaining quality/reliable systems using OSS.
Software Reliability -- NHPP Model and AHP for OSS Reliability Analysis -- NHPP Model and ANP for OSS Reliability Analysis -- Stochastic Differential Equation Models for OSS Reliability Analysis -- Hazard Rates for Embedded OSS Reliability Analysis -- Reliability Analysis for Open Source Solution.
Keywords: Security systems; Mathematical models; Industrial organization; Software engineering; Software engineering -- Management; Security Science and Technology; Mathematical Modeling and Industrial Mathematics; Industrial Organization; Software Engineering; Software Management